2020
DOI: 10.7759/cureus.6681
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Clinical and Radiological Findings and the Outcomes of Early Surgical Treatment After Tossy Type III Acromioclavicular Joint Dislocation

Abstract: Background Acromioclavicular joint (ACJ) dislocation is a common injury among young and physically active persons. Evaluating surgical outcomes clinically and radiographically is widely accepted, but it is not known which clinical tests or radiological indicators are the most important. Our hypothesis is that there is a significant correlation between clinical and radiological findings and outcomes after the early surgical treatment of Tossy type III ACJ dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…They also found that SSV, CS, Taft score, and Acromioclavicular Joint Instability scores improved as the amount of ossification increased, but only the Acromioclavicular Joint Instability score improvement was statistically significant. Another study by Masionis et al 15 reported that patients with ossification had better Simple Shoulder Test scores than those who did not.…”
Section: Discussionmentioning
confidence: 98%
“…They also found that SSV, CS, Taft score, and Acromioclavicular Joint Instability scores improved as the amount of ossification increased, but only the Acromioclavicular Joint Instability score improvement was statistically significant. Another study by Masionis et al 15 reported that patients with ossification had better Simple Shoulder Test scores than those who did not.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, studies have demonstrated that the application of a hook plate had achieved good clinical outcomes despite loss of reduction [31,32]. Although previous studies have shown that clinical outcomes were not directly correlated with radiographic findings based on osteolysis, the relatively high occurrence rate might suggest a disadvantage of hook plate fixation [33]. It was possible that different materials, angles, and depths of hook plates during fixation increased the stress between the plate and acromion, leading to osteolysis of the acromion [7,10,34].…”
Section: Discussionmentioning
confidence: 99%
“…It is stabilized by the tendinous attachments of articular capsule to coracoclavicular ligament, acromioclavicular ligament, trapezius muscle and deltoid muscle. [8][9][10] Some researches have shown that coracoclavicular ligament can affect kinetic equilibrium and static stability of shoulder girdle, independently bear 75% of compressive stress from acromioclavicular joint, and help with clavicle rotation. [11] When acromion is affected by the direct action of top-down violence, the stabilizing device of acromioclavicular joint will be destroyed.…”
Section: Discussionmentioning
confidence: 99%